Recipient Cytotoxic T Lymphocyte Antigen 4 +49 Single-Nucleotide Polymorphism Is Not Associated with Acute Rejection after Liver Transplantation in Chinese Population - Zhijun Jiang, Ying Chen, Xiaonin Feng, Haiyang Xie, Lin Zhou, Shusen Zheng (International Journal of Medical Sciences, 2013)
Objective: Single-nucleotide polymorphisms (SNPs) in Cytotoxic T lymphocyte antigen 4 (CTLA-4) gene have been detected and proved to associate with the incidence of rejection after transplantation. However, previous studies gained inconsistent results about the association between CTLA-4 +49 single-nucleotide polymorphism and susceptibility of allograft rejection. Therefore we sought to clarify whether CTLA-4 +49 SNP influences the incidence of acute rejection after liver transplantation in Chinese population. Methods: Genomic DNA from 335 liver transplant recipients was genotyped for CTLA-4 +49 SNP by DNA sequencing. Acute rejection was confirmed by pathologic evidences. The association between CTLA-4 +49 SNP and incidence of acute rejection was then analyzed by dominant, recessive, codominant and overdominant models. Results: The incidence of acute rejection within the first 3 months was 11.9%. In acute rejectors, the frequency was 45% for G/G, 10% for A/A and 45% for A/G respectively, compared with 47.5% for G/G, 10.8% for A/A and 41.7% for A/G in non-acute rejectors. And no significant difference of allele distribution between these 2 groups was detected. Conclusions: This study suggests that CTLA-4 +49 SNP is not associated with acute rejection after liver transplantation in Chinese population.